Vocational Life Skills Learning Management In Fostering Entrepreneurial Behavior In Deaf Children At SMALB - Khaer, Abu; Wasliman, IIm; Hanafiah, Hanafiah; Dede Khaeriah, N (CV. Inara, 2025)
In this age of globalization, the importance of a quality education must become a foundation. By attaining a desirable education level, job opportunities could be expanded in a competitive era, a feat that is currently difficult for all communities, including high school graduates from special needs schools. In order to provide the social right for people with disabilities, as well as their civil right, and as a solution to prepare human resources, one of the school's programs should prepares its graduates to compete in this society's workforce. This study's objective is to comprehend how